QuEChERS Method for the Determination of Pesticide Residues in Indonesian Green Coffee Beans using Liquid Chromatography Tandem Mass Spectrometry - Harmoko, Harmoko; Kartasasmita, Rahmana Emran; Tresnawati, Astika (Journal of Mathematical and Fundamental Sciences, 2015)
A method using QuEChERS sample preparation followed by liquid chromatography-electrospray ionization-tandem mass spectrometry (LC-ESIMS/MS) was developed for quantitative determination of 14 pesticide residues in Indonesian green coffee beans. The European Standard Method EN 15662:2008 was modified to obtain an appropriate extraction and clean-up procedure for green coffee bean samples. Homogenous slurry samples were extracted with 1% acetic acid in acetonitrile and the extracts were cleaned up by a high pigment dispersive SPE. LC-ESI-MS/MS was operated in the MRM mode for two specific precursor-product ion transitions per target compound to obtain 4 identification points. Representative matrix-matched calibration curves were applied to compensate matrix effects. This method was validated according to the requirements of SANCO/12495/2011. Limits of detection (LODs) and limits of quantification (LOQs) were obtained in the ranges of 0.2-2.9 Î¼g kg-1 and 0.8-9.7 Î¼g kg-1 respectively, showing lower values than the maximum residu limits (MRLs) set by importing countries. The method was applied to determine 14 pesticide residues in 181 Indonesian green coffee bean samples that were taken from different regions. Some pesticide residues were found in these samples and detected to be higher than the MRLs.